Feeding-induced rearrangement of green leaf volatiles reduces moth oviposition - Silke Allmann; Anna Späthe; Sonja Bisch-Knaden; Mario Kallenbach; Andreas Reinecke; Silke Sachse; Ian T Baldwin; Bill S Hansson (eLife, 2013)
The ability to decrypt volatile plant signals is essential if herbivorous insects are to optimize their choice of host plants for their offspring. Green leaf volatiles (GLVs) constitute a widespread group of defensive plant volatiles that convey a herbivory-specific message via their isomeric composition: feeding of the tobacco hornworm Manduca sexta converts (Z)-3- to (E)-2-GLVs thereby attracting predatory insects. Here we show that this isomer-coded message is monitored by ovipositing M. sexta females. We detected the isomeric shift in the host plant Datura wrightii and performed functional imaging in the primary olfactory center of M. sexta females with GLV structural isomers. We identified two isomer-specific regions responding to either (Z)-3- or (E)-2-hexenyl acetate. Field experiments demonstrated that ovipositing Manduca moths preferred (Z)-3-perfumed D. wrightii over (E)-2-perfumed plants. These results show that (E)-2-GLVs and/or specific (Z)-3/(E)-2-ratios provide information regarding host plant attack by conspecifics that ovipositing hawkmoths use for host plant selection.